Digital Transformation in Human Resource Management in Islamic Educational Institutions: A Case Study at MtsN 9 Bantul - Nurul Aisah Samosir; Nurul Istiqomah; Maksudin Maksudin (FKIP - Universitas Riau, 2026)
Digital transformation in human resource management (HRM) has become a strategic necessity for educational institutions to improve governance efficiency, transparency, technology-based service quality, and teacher performance in the era of digital learning. This study aims to analyze the digital transformation process in HRM in Islamic educational institutions with a case study at MTsN 9 Bantul. The approach used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation. Data analysis was conducted interactively through the stages of reduction, presentation, and conclusion drawing. The results show that the implementation of digital transformation at MTsN 9 Bantul includes the use of various platforms such as e-Kinerja, Pusaka, Simpatika, Sigma Masemba, and Jogja Madrasah Digital. Supporting factors include madrasah policy support, human resource competence, and infrastructure readiness, while obstacles arise from technical aspects and limited digital access for some students. Digital transformation has a positive impact on improving discipline, administrative efficiency, data transparency, and institutional reputation. Thus, the application of digital transformation at MTsN 9 Bantul not only improves the effectiveness of human resource management but also strengthens an innovative work culture in the Islamic education environment.